Poetry, Bible and Theology from Late Antiquity to the Middle Ages - Cutino, Michele (Millennium-Studien / Millennium Studies, 2020)
This volume examines for the first time the most important methodological issues concerning Christian poetry - i.e. biblical and theological poetry in classical meters - from a diachronic perspective. Thus, it is possible to evaluate the doctrinal significance of these compositions and the role that they play in the development of Christian theological ideas and biblical exegesis.